Perfil higienicossanitário em uma unidade de dietas especiais de um hospital público de Goiânia, Goiás - Pereira, Ana Cristina de Castro (2016)
Enteral administration is defined as foods for special purposes, by means of probes or orally. It can be industrialized, or manipulated, and according to the nutritional needs, solely or partially, to replace or supplement for oral feeding for patients. Used in hospitals, clinics or homes, with the aim of maintaining tissues, organs or systems. They are an excellent medium for microbial growth, due to its composition rich in nutrients and exposure time at room temperature for administration. Microbial contamination of enteral formulas can occur in several stages, with a critical moment is the manipulation. Thus, this research assessed the hygienic sanitary quality processing of enteral diets and physical and functional adaptations of the Special Diet unit in a public hospital in Goiânia, Goiás. This is an analytical observational design, carried out in three distinct stages: July and November 2015 and January 2016. A checklist has been applied provided the Board of the Resolution n° 63/2000, for situational diagnosis and health of the place. Microbiological analyzes of water were performed, diet powder and reconstituted according to the standards of the Collegiate Board Resolution n° 12/2001 according to the methodology of the American Public Health Association. It also investigated the presence of Staphylococcus aureus and Escherichia coli in hands and nostrils of the handlers involved in the preparation of diets. For statistical analysis, for the qualitative and discrete variables, we used the Q Test Cochran, while for the quantitative variables we used the Friedmann test. The reconstituted diet was coliforms at 35 °C in 78% of samples, but not confirmed E. coli and coagulase positive Staphylococci counts at any stage. The powder preparation diet and water at all stages, there were no contamination by pathogenic micro-organisms. It detected the presence of S. aureus and E. coli in hands (10% for both micro-organisms) and nasal cavity (10% and 41%, respectively) of the surveyed handlers. Considering the checklist for inspection preparation of diets in the UDE, the average rate of compliance of blocks evaluated was 64.9%, 62.7% and 74.6% in the stages of the study, respectively. The hygienic sanitary profile was partially unsatisfactory. The main problems identified were enteral feedings reconstituted outside the microbiological standards for coliforms at 35 °C, but without the presence of pathogenic micro-organisms. There was inadequate microbiological profile of hands and nostrils of some manipulators and low compliance rates in some blocks, indicating a need for readjusting the physical structure, better quality control record of the manipulated diets and reassessment of the handlers hygiene practices, since this can be seen as one of the important factors in the transmission of diseases, and responsible for foodborne outbreaks.